2014
DOI: 10.3389/fnagi.2014.00315
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status Evaluation in Patients Affected by Bethlem Myopathy and Ullrich Congenital Muscular Dystrophy

Abstract: Collagen VI mutations lead to disabling myopathies like Bethlem myopathy (BM) and Ullrich congenital muscular dystrophy (UCMD). We have investigated the nutritional and metabolic status of one UCMD and seven BM patients (five female, three male, mean age 31 ± 9 years) in order to find a potential metabolic target for nutritional intervention. For this study, we used standard anthropometric tools, such as BMI evaluation and body circumference measurements. All results were compared to dual-energy X-ray absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…In all three groups of patients sarcopenia co-existed with obesity as previously described in adult patients ( Merlini et al, 2014 ). Also, similar to what other authors have reported, there was no deviation from normal in the mean BMI which may be explained by the loss of muscle mass and the fatty infiltration of skeletal muscle ( Toni et al, 2014 ) and which highlights the usefulness of the determination of total fat mass by DXA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In all three groups of patients sarcopenia co-existed with obesity as previously described in adult patients ( Merlini et al, 2014 ). Also, similar to what other authors have reported, there was no deviation from normal in the mean BMI which may be explained by the loss of muscle mass and the fatty infiltration of skeletal muscle ( Toni et al, 2014 ) and which highlights the usefulness of the determination of total fat mass by DXA.…”
Section: Discussionsupporting
confidence: 89%
“…There are two other studies looking at body composition by DXA in patients with collagen VI deficiency although both look at the same cohort composed of one adult UCMD and seven adult BM patients ( Miscione et al, 2013 ; Toni et al, 2014 ). In those studies they use as the reference population a cohort of healthy individuals from the United States ( Kelly et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results were compared with validated, published normal controls, as has been done previously in similarly published cohort studies. [27][28][29] Manual muscle testing. After completion of the muscle strength testing via handheld dynamometry, manual muscle testing (MMT) was completed in the following muscle groups: hip flexors, knee extensors, hip abductors, hip extensors, and knee flexors bilaterally.…”
Section: Muscle Strengthmentioning
confidence: 99%
“…To address how ECM affects adipogenesis and adipocyte function, Type I collagen-based hydrogel can be utilized to mimic physiologically relevant adipogenic microenvironments, since it can be modified in terms of biophysical and biochemical properties [ 112 ]. Tissue culture plastic coated with type I collagen has been reported to enhance adipogenesis [ 113 ], while type VI collagen appears to restrict adipose expansion [ 114 ]. Interestingly, by blocking an attachment of integrin alpha 6 to laminin, it allowed differentiation of adipocytes due to sustained anti-adipogenic RhoA activity [ 115 ].…”
Section: Modeling Adipogenesis Via Three-dimensional (3d) Culturementioning
confidence: 99%